Impact of gastric pH profiles on the proteolytic digestion of mixed βlg-Xanthan biopolymer gels. Issue 1 (24th November 2015) - Dekkers, B. L.; Kolodziejczyk, E.; Acquistapace, S.; Engmann, J.; Wooster, T. J.
Abstract : Gastric pH profile during in vitro gastric digestion is critical for proper assessment of mixed biopolymer gel proteolysis. Abstract : The understanding of how foods are digested and metabolised is essential to enable the design/selection of foods as part of a balanced diet. Essential to this endeavour is the development of appropriate biorelevant in vitro digestion tools. In this work, the influence of gastric pH profile on the in vitro digestion of mixtures of β-lactoglobulin (βlg) and xanthan gum prior to and after heat induced gelation was investigated. A conventional highly acidic (pH 1.9) gastric pH profile was compared to two dynamic gastric pH profiles (initial pH of 6.0 vs . 5.2 and H + secretion rates of 60 vs . 36 mmol h −1 ) designed to mimic the changes in gastric pH observed during clinical trials with high protein meals. In moving away from the pH 1.9 model, to a pH profile reflecting in vivo conditions, the initial rate and degree of protein digestion halved during the first 45 minutes. After 90 minutes of gastric digestion, all three pH profiles caused similar extents of protein digestion. Given that 50% gastric emptying times of (test) meals are in range of 30–90 min, it would seem highly relevant to use a dynamic pH gastric model rather than a pH 1.9 (USP) or pH 3 model (INFOGEST) in assessing the impact of food structuring approaches on protein digestion. The impact that heat induced gelation had on the degree of gel digestion by pepsin was also investigated. Surprisingly, it was found that heat induced gelation of βlg-xanthan mixtures at 70–90 °C for 20 minutes lead to a considerable decrease in the rate of proteolysis, which contrasts many studies of dispersed aggregates and gels of βlg alone whose heating accelerates pepsin activity due to unfolding. In the present case, the formation of a dense protein network created a fine pore structure which restricted pepsin access into the gel thereby slowing proteolysis. This work not only has implications for the in vitro assessment of protein digestion, but also highlights how protein digestion might be slowed, learnings that might have an influence on the design of foods as part of a satisfying balanced diet.